The Effect of Trust and Service Quality on Customer Loyalty of Goods Delivery Services : (Case Study at PT. Tiki Jalur Nugraha Ekakurir) - Muhammad Chalid Rasyidy; Widayat Widayat; Sri Nastiti Andharini (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
This study aims to determine how the influence of trust and service quality on customer loyalty of PT. Tiki Jalur Nugraha Ekakurir (PT. JNE). This research was conducted on customers who have used freight forwarding services in JNE, located at Jl. Pajajaran 17B, Malang City with the number of respondents taken using accidental sampling techniques so that the number of respondents was 100 people. Data collection using questionnaires and data measurement used is the Likert scale. The test instruments in this study were validity and reliability tests, and for data analysis techniques used classical assumption tests, multiple linear regression analysis and hypothesis testing. The results of this study can be seen that there is a positive and significant partial influence between trust and service quality on customer loyalty. The simultaneous influence of the variable trust and service quality has a significant and positive effect on customer loyalty of PT. Tiki Jalur Nugraha Ekakurir.